1985
DOI: 10.1016/0378-1097(85)90093-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen in Methanolobus and Methanococcus

Abstract: Glycogen was isolated from Methanolobus tindarius and 4 species of Methanococcus. It was identified by the iodine reaction, determination of glucose, maltose and isomaltose in acid hydrolysates and partial acid hydrolysates, respectively, determination of erythritol and glycerol after periodate oxidation and treatment with amyloglucosidase. Glycogen particles in the cells are distributed throughout the cytoplasm. Ml. tindarius can use elemental nitrogen and cysteine as nitrogen source. The glycogen and polypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…Sibold et al (27) reported hybridization between eubacterial nifHDK probes and DNA from four different methanogenic species. These discoveries were the first confirmed examples of diazotrophy among members of the archaebacteria and have been followed by other descriptions of nitrogen-fixing methanogenic archaebacteria (1,9,13,18 There have been several recent studies on the physiology of diazotrophy in methanogens (1,3,16,18,25). In our previous study on M. barkeri 227 (16) we found similarities to the process in eubacteria, including significant decreases in growth yields and rates when N2 was the N source, stimulation of diazotrophic growth by Mo, and switch-off of C2H2-reducing activity in response to added NH4+.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Sibold et al (27) reported hybridization between eubacterial nifHDK probes and DNA from four different methanogenic species. These discoveries were the first confirmed examples of diazotrophy among members of the archaebacteria and have been followed by other descriptions of nitrogen-fixing methanogenic archaebacteria (1,9,13,18 There have been several recent studies on the physiology of diazotrophy in methanogens (1,3,16,18,25). In our previous study on M. barkeri 227 (16) we found similarities to the process in eubacteria, including significant decreases in growth yields and rates when N2 was the N source, stimulation of diazotrophic growth by Mo, and switch-off of C2H2-reducing activity in response to added NH4+.…”
mentioning
confidence: 68%
“…Sibold et al (27) reported hybridization between eubacterial nifHDK probes and DNA from four different methanogenic species. These discoveries were the first confirmed examples of diazotrophy among members of the archaebacteria and have been followed by other descriptions of nitrogen-fixing methanogenic archaebacteria (1,9,13,18). The existence of archaebacterial diazotrophy raises the following question: in light of the structural and functional homology among eubacterial nitrogenases, would archaebacterial nitrogenases be similar to them, or would they have subtle or major differences?…”
mentioning
confidence: 68%
“…This microbial ecosystem was selected to investigate, among other questions, whether, under this approach, a hypothetic microorganism capable of producing methane directly from glucose would be competitive over the experimentally reported volatile fatty acid (VFAs) synthesizers in synergy with methane-producing archaea. Methanogens have been reported to possess the biochemical mechanisms to metabolize carbohydrates (König et al, 1985;Murray and Zinder, 1987); however, there is no experimental evidence of any microorganism producing methane directly from a carbohydrate as substrate (Schink, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Several of these enzymes, including a glycogen debranching enzyme and predicted alpha-1,6-glucosidase activity, are not present in any other known members of class Halobacteria. However, these enzyme activities are frequently found in archaea from classes Methanococci and Thermoplasmata that utilize starch as an internal storage molecule (Kö nig et al, 1985(Kö nig et al, , 1982. This suggests a possible common ancestral origin, with subsequent gene loss in the Halobacteria lineage.…”
Section: Genome Characteristics Of J07ab43 and J07ab56mentioning
confidence: 99%